3D filter material and method for producing the same

CN119567666BActive Publication Date: 2026-10-09ZHEJIANG SHENGLAN NEW MATERIAL&TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411624424.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2026-10-09
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

[0004]为了克服现有技术中3D过滤材料存在热压复合面积大容尘量小的问题,本发明提供了一种3D过滤材料及其制备方法,该材料包括复合端和与复合端相邻的过滤端构成,复合端采用热压复合制成,复合端将多层纤维层复合层一个整体,未经过压合的部位不会受到影响,能够避免使用胶粘剂复合会减少3D过滤材料容尘量和吸液性能的问题

Benefits of technology

本发明提供了一种3D过滤材料及其制备方法,该材料包括复合端和与复合端相邻的过滤端构成,复合端采用热压复合制成,复合端将多层纤维层复合层一个整体,未经过压合的部位不会受到影响,能够避免使用胶粘剂复合会减少3D过滤材料容尘量和吸液性能的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005134335470000071
    Figure BDA0005134335470000071
  • Figure BDA0005134335470000081
    Figure BDA0005134335470000081
Patent Text Reader

Abstract

The application relates to the technical field of filtering materials, and discloses a 3D filtering material and a preparation method thereof. The material comprises a composite end and a filtering end adjacent to the composite end, the filtering end comprises a plurality of stacked fiber layers, and the composite end is made by hot-pressing compounding of the fiber layers. The composite end of the material integrates the plurality of fiber layers into a whole, the parts not subjected to the pressing and compounding are not affected, the problem that the dust capacity and the liquid absorption performance of the 3D filtering material are reduced due to the use of adhesive for compounding can be avoided, and the material has high compounding strength and high dust capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of filter materials technology, and in particular to a 3D filter material and its preparation method. Background Technology

[0002] 3D filter materials are commonly used to separate water from other substances, such as wiping cloths, absorbent pads in sanitary materials, and filter cartridges in oil-water separators. They are three-dimensional structures with dense pores made of fibers. When in use, water molecules are absorbed into the fiber pores through capillary action formed by the pore structure between the fibers, thus separating water from other substances. 3D filter materials only collect water through their pore structure, and the water in the 3D filter material still needs to be discharged afterward. Therefore, the pore structure between the fibers and the proportion of space formed by it have a significant impact on the water content that the 3D filter material can hold.

[0003] Existing 3D filter materials primarily use natural cotton and polyester fibers. However, natural cotton fibers have poor high-temperature and acid / alkali resistance, making them unsuitable for use in high-temperature and acid / alkali environments. While polyester fibers offer strong high-temperature and acid / alkali resistance, they are less flexible than natural cotton fibers. Therefore, to achieve multiple functions such as high-temperature resistance, acid / alkali resistance, and flexibility in 3D filter materials, fibers with different functions are typically composited, as seen in technical solutions such as CN112726058A and CN102162173B. However, due to the significant differences in the properties of fibers with different functions, the composite material exhibits low strength and is easily damaged. The existing technology uses adhesives for bonding and bonding, but adhesives can easily form barrier interfaces after use, leading to a decrease in the liquid absorption performance of 3D filter materials. In addition, the existing technology also proposes to modify the fibers and then use hot pressing to bond the modified fibers together, but different fibers still have poor compatibility and low composite strength. Therefore, it is necessary to increase the hot pressing composite area to improve the composite strength. However, if the hot pressing composite area is too large, it will reduce the dust holding capacity of the 3D filter material. Therefore, how to ensure the composite strength while reducing the hot pressing composite area is of great significance for increasing the dust holding capacity of 3D filter materials. Summary of the Invention

[0004] To overcome the problem of large hot-pressed composite area and small dust holding capacity in existing 3D filter materials, this invention provides a 3D filter material and its preparation method. The material consists of a composite end and a filter end adjacent to the composite end. The composite end is made by hot-pressing composite, which combines multiple fiber layers into a whole. Parts that have not been pressed will not be affected, thus avoiding the problem that the use of adhesives will reduce the dust holding capacity and liquid absorption performance of the 3D filter material.

[0005] The specific technical solution of this invention is as follows: A 3D filter material includes a composite end and a filter end adjacent to the composite end. The filter end includes several stacked fiber layers, and the composite end is made by hot-pressing the fiber layers together.

[0006] This invention provides a 3D filter material, which includes a composite end and a filter end adjacent to the composite end. The filter end is made of several stacked fiber layers, and the composite end is made by hot-pressing the fiber layers together. This material does not use adhesives for bonding, thus increasing dust holding capacity and significantly improving washing liquid performance.

[0007] A method for preparing the above-mentioned 3D filter material includes the following steps: stacking fiber layers and then hot-pressing them with a roller to form a 3D filter material, wherein the hot-pressing temperature is 50-200℃.

[0008] This invention provides a method for preparing the above-mentioned 3D filter material. The method uses a patterned roller to hot-press the stacked fiber layers. The raised part of the patterned roller heats and presses the fiber layers to form composite ends, while the concave part of the patterned roller does not press the fiber layers, so that the volume of the stacked fiber layers is not affected. This application combines materials with different properties by heating and pressing, which can avoid the problem that adhesive bonding will reduce the dust holding capacity and liquid absorption performance of the 3D filter material.

[0009] Preferably, the material of the fiber layer includes one or more of PBT fiber layer, PP fiber layer and natural fiber layer.

[0010] Preferably, the PBT fiber layer is made by melt spinning PBT resin, which is made by copolymerizing terephthalic acid and 1,4-butanediol as raw materials under the conditions of modifier and catalyst. The copolymerization reaction includes esterification reaction, prepolymerization reaction and polycondensation reaction in sequence.

[0011] Preferably, the modifier is a diacid, a diol, or acrylic acid.

[0012] Preferably, the molar ratio of the dicarboxylic acid, diol, and acrylic acid is 1:2 to 2.5:1 to 2.

[0013] Preferably, the dicarboxylic acid is one or both of isophthalic acid and adipic acid, and the diol is hexanediol.

[0014] This invention modifies PBT polyester, lowering the melting point of the modified PBT fibers to 150-160°C. When PBT fiber layers and PP fiber layers made from PBT polyester are hot-pressed together to form a 3D filter material, the overall structure formed by the melting of the PBT fiber layers and PP fibers exhibits excellent compatibility. This significantly reduces the pressing area while ensuring the composite strength of the 3D filter material meets standards, significantly increases the volume of the filter end, significantly improves the dust holding capacity of the 3D filter material, and enhances the liquid absorption performance of the material. The modifiers used in this invention are diacid, diol, and acrylic acid. Adding diacid and diol during the PBT copolymerization stage introduces flexible segments into the PBT copolyester molecular chain, thereby lowering the melting point of PBT and bringing it closer to that of PP. This allows the fiber layers to melt and composite rapidly at a low temperature of around 150°C. Furthermore, this invention found that adding acrylic acid further increases the compatibility between PBT and PP, significantly improving the composite strength of the PBT and PP.

[0015] Preferably, the molar ratio of terephthalic acid to 1,4-butanediol is 1.3–1.8:2.6–3.

[0016] Preferably, the catalyst is one or more of tetrabutyl titanate, isopropyl titanate, and titanium glycol.

[0017] Preferably, the conditions for the esterification reaction include: a first-stage esterification reaction temperature of 160–190°C and a first-stage esterification reaction time of 1–3 h; a second-stage esterification reaction temperature of 190–220°C and a second-stage esterification reaction time of 1–2 h; the conditions for the prepolymerization reaction include: a first-stage prepolymerization reaction temperature of 220–240°C and a first-stage prepolymerization reaction time of 0.5–1 h; a first-stage prepolymerization reaction pressure of 1–10 kPa; a second-stage prepolymerization reaction temperature of 240–250°C and a second-stage prepolymerization reaction time of 0.5–1 h; and the conditions for the polycondensation reaction include: a polycondensation reaction temperature of 250–270°C; a polycondensation reaction pressure of 0.01–0.1 kPa; and a polycondensation reaction time of 1.5–3 h.

[0018] Compared with the prior art, this application has the following technical effects: This invention provides a 3D filter material and its preparation method. The material comprises a composite end and a filter end adjacent to the composite end. The composite end is made by hot pressing. The composite end combines multiple fiber layers into a whole. Parts that have not been pressed will not be affected. This avoids the problem that using adhesives to bond the 3D filter material will reduce its dust holding capacity and liquid absorption performance. Detailed Implementation

[0019] The present invention will be further described below with reference to embodiments.

[0020] Example 1: A 3D filter material includes a composite end and a filter end adjacent to the composite end. The filter end includes PP polyester fibers, filter paper fibers and PP polyester fibers stacked in sequence. The composite end is made by hot pressing the fiber layers together. A method for preparing the above-mentioned 3D filter material includes the following steps: PP polyester is made into PP meltblown cloth using the meltblown method. Holes are cut into the surface of filter paper to form an intermediate layer. The PP meltblown cloth, intermediate layer and PP meltblown cloth are then stacked to form a preform. The preform is then hot-pressed with a patterned roller. The hot-pressing point is located at the holes in the intermediate layer. The hot-pressing temperature is 130℃. After hot pressing, 3D filter material is produced.

[0021] Example 2: A 3D filter material includes a composite end and a filter end adjacent to the composite end. The filter end includes PP polyester fibers, absorbent paper and PP polyester fibers stacked in sequence. The composite end is made by hot pressing the fiber layers together. A method for preparing the above-mentioned 3D filter material includes the following steps: PP polyester is made into PP meltblown fabric using the meltblown method. Holes are cut into the surface of absorbent paper to form an intermediate layer. The PP meltblown fabric, intermediate layer and PP meltblown fabric are then stacked to form a preform. The preform is then hot-pressed with a patterned roller. The hot-pressing point is located at the holes in the intermediate layer. The hot-pressing temperature is 50℃. After hot pressing, a 3D filter material is produced.

[0022] Example 3: A 3D filter material includes a composite end and a filter end adjacent to the composite end. The filter end includes PBT polyester fibers, PP polyester fibers and PBT polyester fibers stacked in sequence. The composite end is made by hot pressing the fiber layers together. A method for preparing the above-mentioned 3D filter material includes the following steps: Preparation of PBT polyester: 270g of 1,4-butanediol, 300g of terephthalic acid, 130g of adipic acid, 80g of isophthalic acid, 59g of hexanediol, 36.03g of acrylic acid, and 0.34g of tetrabutyl titanate were added to a reactor for polymerization to produce PBT polyester. Nitrogen gas was introduced into the reactor to purge the air, and the pressure was increased to 0.1MPa. The polymerization reaction sequentially included esterification, prepolymerization, and polycondensation. The esterification process involved heating to 160–190℃ for a first-stage esterification reaction and reacting for 1–3 seconds. h, then raise the temperature to 160-190℃ for a second-stage esterification reaction and react for 1-2 hours; after the esterification reaction is completed, a prepolymerization reaction is carried out, which includes: raising the temperature to 220-240℃ for a first-stage prepolymerization reaction and reacting for 0.5-1 hours, then raising the temperature to 240-250℃ and then increasing the pressure to 0.5-1 kPa for a second-stage prepolymerization reaction and reacting for 0.5-1 hours; after the prepolymerization reaction is completed, a polycondensation reaction is carried out, with the following conditions: raising the temperature to 250-270℃ and decreasing the pressure to 0.01-0.1 kPa for a polycondensation reaction and reacting for 1.5-3 hours; Preparation of 3D filter material: PBT polyester is made into PBT meltblown cloth by meltblowing method, and PP polyester is made into PP meltblown cloth by meltblowing method. PBT meltblown cloth, PP meltblown cloth and PBT meltblown cloth are stacked in sequence to form a preform. Then, the preform is hot-pressed and laminated using a patterned roller at a temperature of 170℃ and a hot-pressed area ratio of 0.5%. After cooling and winding, 3D filter material is produced.

[0023] Example 4: A 3D filter material includes a composite end and a filter end adjacent to the composite end. The filter end includes PBT polyester fibers, PP polyester fibers and PBT polyester fibers stacked in sequence. The composite end is made by hot pressing the fiber layers together. A method for preparing the above-mentioned 3D filter material includes the following steps: Preparation of PBT polyester: 270g of 1,4-butanediol, 300g of terephthalic acid, 130g of adipic acid, 80g of isophthalic acid, 47.2g of hexanediol, 72.06g of acrylic acid, and 0.34g of tetrabutyl titanate were added to a reactor for polymerization to produce PBT polyester. Nitrogen gas was introduced into the reactor to purge the air, and the pressure was increased to 0.1MPa. The polymerization reaction sequentially included esterification, prepolymerization, and polycondensation. The esterification process involved heating to 160–190℃ for a first-stage esterification reaction and reacting for 1–2 minutes. After 3 hours, the temperature is raised to 160–190℃ for a second-stage esterification reaction and the reaction continues for 1–2 hours. After the esterification reaction is completed, a prepolymerization reaction is carried out, which includes: raising the temperature to 220–240℃ for a first-stage prepolymerization reaction and the reaction continues for 0.5–1 hours, then raising the temperature to 240–250℃ and the pressure to 0.5–1 kPa for a second-stage prepolymerization reaction and the reaction continues for 0.5–1 hours. After the prepolymerization reaction is completed, a polycondensation reaction is carried out, with the following conditions: raising the temperature to 250–270℃ and lowering the pressure to 0.01–0.1 kPa for a polycondensation reaction and the reaction continues for 1.5–3 hours. Preparation of 3D filter material: PBT polyester is made into PBT meltblown cloth by meltblowing method, and PP polyester is made into PP meltblown cloth by meltblowing method. PBT meltblown cloth, PP meltblown cloth and PBT meltblown cloth are stacked in sequence to form a preform. Then, the preform is hot-pressed and laminated using a patterned roller at a temperature of 170℃ and a hot-pressed area ratio of 0.3%. After cooling and winding, 3D filter material is produced.

[0024] Example 5: A 3D filter material includes a composite end and a filter end adjacent to the composite end. The filter end includes PBT polyester fibers, PP polyester fibers and PBT polyester fibers stacked in sequence. The composite end is made by hot pressing the fiber layers together. A method for preparing the above-mentioned 3D filter material includes the following steps: Preparation of PBT polyester: 270g of 1,4-butanediol, 300g of terephthalic acid, 130g of adipic acid, 80g of isophthalic acid, 52.44g of hexanediol, 48.04g of acrylic acid, and 0.34g of tetrabutyl titanate were added to a reactor for polymerization to produce PBT polyester. Nitrogen gas was introduced into the reactor to purge the air, and the pressure was increased to 0.1MPa. The polymerization reaction sequentially included esterification, prepolymerization, and polycondensation. The esterification process involved heating to 160–190℃ for a first-stage esterification reaction and reacting for 1 minute. After 1-3 hours, the temperature is raised to 160-190℃ for a second-stage esterification reaction and the reaction continues for 1-2 hours. After the esterification reaction is completed, a prepolymerization reaction is carried out, which includes: raising the temperature to 220-240℃ for a first-stage prepolymerization reaction and the reaction continues for 0.5-1 hours, then raising the temperature to 240-250℃ and the pressure to 0.5-1 kPa for a second-stage prepolymerization reaction and the reaction continues for 0.5-1 hours. After the prepolymerization reaction is completed, a polycondensation reaction is carried out, with the following conditions: raising the temperature to 250-270℃ and lowering the pressure to 0.01-0.1 kPa for a polycondensation reaction and the reaction continues for 1.5-3 hours. Preparation of 3D filter material: PBT polyester is made into PBT meltblown cloth by meltblowing method, and PP polyester is made into PP meltblown cloth by meltblowing method. PBT meltblown cloth, PP meltblown cloth and PBT meltblown cloth are stacked in sequence to form a preform. Then, the preform is hot-pressed and laminated using a patterned roller at a temperature of 170℃ and a hot-pressed area ratio of 0.1%. After cooling and winding, 3D filter material is produced.

[0025] Comparative Example 1: Compared to Example 1, Comparative Example 1 used an adhesive to laminate the fiber layer, with an adhesive application rate of 0.2 g / m². 2 .

[0026] Comparative Example 2: Compared to Example 2, Comparative Example 1 used an adhesive to laminate the fiber layer, with an adhesive application rate of 0.2 g / m². 2 .

[0027] Comparative Example 3: Compared with Examples 3-5, Comparative Example 3 used an adhesive to composite the fiber layer, with an adhesive application rate of 0.2 g / m². 2 .

[0028] Comparative Example 4: Compared with Examples 3-5, the PBT in Comparative Example 4 was not modified, and the hot-pressed area accounted for 30%.

[0029] A 3D filter material includes a composite end and a filter end adjacent to the composite end. The filter end includes PBT polyester fibers, PP polyester fibers and PBT polyester fibers stacked in sequence. The composite end is made by hot pressing the fiber layers together. A method for preparing the above-mentioned 3D filter material includes the following steps: Preparation of PBT polyester: 270g of 1,4-butanediol, 300g of terephthalic acid, 130g of adipic acid, and 0.34g of tetrabutyl titanate were added to a reactor for polymerization to produce PBT polyester. Nitrogen gas was introduced into the reactor to purge the air, and the pressure was increased to 0.1MPa. The polymerization reaction sequentially included esterification, prepolymerization, and polycondensation. The esterification process was as follows: a first-stage esterification reaction was carried out at 160–190℃ for 1–3 hours, followed by further heating to 160–190℃. A two-stage esterification reaction is carried out for 1–2 hours. After the esterification reaction is completed, a prepolymerization reaction is carried out, which includes: heating to 220–240℃ for a first-stage prepolymerization reaction for 0.5–1 hour, then heating to 240–250℃ and pressurizing to 0.5–1 kPa for a second-stage prepolymerization reaction for 0.5–1 hour. After the prepolymerization reaction is completed, a polycondensation reaction is carried out, with the following conditions: heating to 250–270℃ and depressurizing to 0.01–0.1 kPa for a polycondensation reaction for 1.5–3 hours. Preparation of 3D filter material: PBT polyester is made into PBT meltblown cloth by meltblowing method, and PP polyester is made into PP meltblown cloth by meltblowing method. PBT meltblown cloth, PP meltblown cloth and PBT meltblown cloth are stacked in sequence to form a preform. Then, the preform is hot-pressed and laminated using a patterned roller at a temperature of 170℃ and a hot-pressed area ratio of 30%. After cooling and winding, 3D filter material is produced.

[0030] Comparative Example 5: Compared with Examples 3-5, the modifier in Comparative Example 5 does not contain acrylic acid, and the hot-pressed area accounts for 5%.

[0031] A 3D filter material includes a composite end and a filter end adjacent to the composite end. The filter end includes PBT polyester fibers, PP polyester fibers and PBT polyester fibers stacked in sequence. The composite end is made by hot pressing the fiber layers together. A method for preparing the above-mentioned 3D filter material includes the following steps: Preparation of PBT polyester: 270g of 1,4-butanediol, 300g of terephthalic acid, 130g of adipic acid, 80g of isophthalic acid, 59g of hexanediol, and 0.34g of tetrabutyl titanate were added to a reactor for polymerization to produce PBT polyester. Nitrogen gas was introduced into the reactor to purge the air, and the pressure was increased to 0.1MPa. The polymerization reaction sequentially included esterification, prepolymerization, and polycondensation. The esterification process was as follows: a first-stage esterification reaction was carried out at 160–190℃ for 1–3 hours, followed by further heating. A two-stage esterification reaction is carried out at 160–190℃ for 1–2 hours. After the esterification reaction, a prepolymerization reaction is carried out, which includes: heating to 220–240℃ for a first-stage prepolymerization reaction for 0.5–1 hour, then heating to 240–250℃ and pressurizing to 0.5–1 kPa for a second-stage prepolymerization reaction for 0.5–1 hour. After the prepolymerization reaction, a polycondensation reaction is carried out, with the following conditions: heating to 250–270℃ and depressurizing to 0.01–0.1 kPa for a polycondensation reaction for 1.5–3 hours. Preparation of 3D filter material: PBT polyester is made into PBT meltblown cloth by meltblowing method, and PP polyester is made into PP meltblown cloth by meltblowing method. PBT meltblown cloth, PP meltblown cloth and PBT meltblown cloth are stacked in sequence to form a preform. Then, the preform is hot-pressed and laminated using a patterned roller at a temperature of 170℃ and a hot-pressed area ratio of 5%. After cooling and winding, 3D filter material is produced.

[0032] Comparative Example 6: Compared with Examples 3-5, the modifier in Comparative Example 6 does not contain acrylic acid, and the hot-pressing area accounts for 1%.

[0033] A 3D filter material includes a composite end and a filter end adjacent to the composite end. The filter end includes PBT polyester fibers, PP polyester fibers and PBT polyester fibers stacked in sequence. The composite end is made by hot pressing the fiber layers together. A method for preparing the above-mentioned 3D filter material includes the following steps: Preparation of PBT polyester: 270g of 1,4-butanediol, 300g of terephthalic acid, 130g of adipic acid, 80g of isophthalic acid, 59g of hexanediol, and 0.34g of tetrabutyl titanate were added to a reactor for polymerization to produce PBT polyester. Nitrogen gas was introduced into the reactor to purge the air, and the pressure was increased to 0.1MPa. The polymerization reaction sequentially included esterification, prepolymerization, and polycondensation. The esterification process was as follows: a first-stage esterification reaction was carried out at 160–190℃ for 1–3 hours, followed by further heating. A two-stage esterification reaction is carried out at 160–190℃ for 1–2 hours. After the esterification reaction, a prepolymerization reaction is carried out, which includes: heating to 220–240℃ for a first-stage prepolymerization reaction for 0.5–1 hour, then heating to 240–250℃ and pressurizing to 0.5–1 kPa for a second-stage prepolymerization reaction for 0.5–1 hour. After the prepolymerization reaction, a polycondensation reaction is carried out, with the following conditions: heating to 250–270℃ and depressurizing to 0.01–0.1 kPa for a polycondensation reaction for 1.5–3 hours. Preparation of 3D filter material: PBT polyester is made into PBT meltblown cloth by meltblowing method, and PP polyester is made into PP meltblown cloth by meltblowing method. PBT meltblown cloth, PP meltblown cloth and PBT meltblown cloth are stacked in sequence to form a preform. Then, the preform is hot-pressed and laminated using a patterned roller at a temperature of 170℃ and a hot-pressed area ratio of 1%. After cooling and winding, 3D filter material is produced.

[0034] Detection example The 3D filter materials prepared in Examples 1 to 5 and Comparative Examples 1 to 6 were tested for peel strength and dust holding capacity. Dust holding capacity test method: Cut the 3D filter material into a sample with a length of 100mm and a width of 100mm, weigh the initial weight of the sample, place the sample in the test liquid for 5 minutes, take it out and place it on a mesh-like water platform for 1 minute to measure the moisture absorption weight. The dust holding capacity is the difference between the moisture absorption weight and the initial weight, in g. The glass strength test method refers to "GB 8808-88 Peel Test Method for Flexible Composite Plastic Materials"; the test steps include: removing 50mm from both ends of the sample width direction, uniformly cutting 5 longitudinal and 5 transverse samples along the sample width direction, with the composite direction being longitudinal; peeling the composite layer 50mm apart along the sample length direction, ensuring the peeled part is not obviously damaged; placing the sample in an environment of 23±2℃ and relative humidity of 45~55% for more than 4 hours, and then conducting the test in this environment; clamping both ends of the peeled part of the sample onto the upper and lower clamps of the testing machine, aligning the longitudinal axis of the peeled part with the center line of the upper and lower clamps, and ensuring appropriate tightness; recording the peel curve of the glass process in a T-shape with the tensile direction for the unpeeled part; the test speed is 200±50mm / min; calculating the arithmetic mean of each group of samples, in N.

[0035] The test results are shown in Table 1; Table 1 Test Results As shown in Table 1, in Examples 1 and 2, the intermediate layer was perforated, and then the fiber layer was hot-pressed at the perforated position of the intermediate layer. The peel strength of Examples 1 and 2 was 10-12 N, and the dust holding capacity was 253-563 g. In contrast, Comparative Examples 1 and 2 were materials composited using adhesives. The peel strength of Comparative Examples 1 and 2 was only 4-5 N, and the dust holding capacity was only 181-430 g. The above results show that after perforating the intermediate layer of the 3D material obtained in this application, the fiber layers of the same material on both sides of the two intermediate layers can be bonded together. The compatibility of the same material is better when hot-pressed. Therefore, the composite strength of the material can be significantly improved after hot pressing, which is significantly higher than that of the material using adhesives.

[0036] Furthermore, this application has discovered that the method of perforation followed by lamination has a significant impact on the hot-pressing lamination area due to the size of the perforation. The size of the perforation requires high precision in both the material and the perforation device. It also requires the provision of a patterned roller corresponding to the perforation, making the process quite complex. Moreover, the perforation is usually large, resulting in a large hot-pressing lamination area and a large dust holding capacity of the disclosed material. Therefore, based on the above, embodiments 3 to 5 are provided.

[0037] In Examples 3 to 5, modified PBT polyester and PP polyester were used to make 3D materials. PP polyester was used as an intermediate layer, and modified PBT polyester was located in two layers of the intermediate layer. The modified PBT polyester was a low-melting-point PBT polyester modified with a modifier and had excellent compatibility with PP polyester. During hot pressing, PBT fibers and PP fibers melted and fused into a whole, and the composite strength was significantly improved compared with ordinary composite interfaces.

[0038] Comparative Example 3 is a 3D filter material using adhesive, with a peel strength of only 6N and a dust holding capacity of only 258g, which is significantly lower than Examples 3 to 5 (peel strength of only 15-18N and dust holding capacity of only 292-311g). The above results indicate that the 3D filter material provided by the present invention can significantly improve the composite strength and dust holding capacity of the 3D filter material compared with the adhesive composite method.

[0039] In Comparative Example 4, the PBT without a modifier had a peel strength of only 7N and a dust holding capacity of only 203g, significantly lower than Examples 3 to 5. Analysis revealed that the melting temperature of the unmodified PBT polyester was higher. Therefore, when the fibers were composited at a hot-pressing temperature of 150°C, only the PP polyester melted, while the PBT polyester did not. After the PP polyester melted, it solidified and composited with the PBT fibers. Due to the poor compatibility between the PP polyester and the unmodified PBT polyester, the hot-pressing area needed to be increased to 30% to achieve a peel strength of 7N. However, the dust holding capacity decreased to 203g, a significant reduction.

[0040] In Comparative Example 5, no acrylic acid was added to the modifier. When the hot-pressing area of ​​Comparative Example 5 reached 5%, its peel strength reached 6 N, and its dust holding capacity was 286 g. Although modifying PBT polyester to low-melting-point PBT polyester allows PBT and PP fibers to melt simultaneously and form a denser structure, the poor compatibility between PBT polyester and PP polyester results in a still low composite strength after melting and mixing. A hot-pressing area of ​​at least 5% is still needed to achieve good composite strength. The dust holding capacity and composite strength are still significantly lower than in Examples 3 to 5. In Comparative Example 6, no acrylic acid was added to the modifier. When the hot-pressing area was reduced to 1%, the peel strength was only 3 N, a significant decrease. Analysis of Comparative Example 5, Comparative Example 6, and Examples 3 to 5 reveals that PBT polyester and PP… The composite strength of the composite formed by melting and mixing polyester is higher than that of the composite interface formed by PBT fiber and PP polyester. To improve the composite strength, the area of ​​the composite interface needs to be increased. However, increasing the area of ​​the composite interface will reduce the dust holding capacity of the material. Therefore, the composite formed by melting the materials can reduce the composite area while ensuring the composite strength, thereby increasing the dust holding capacity of the material. The composite strength of the composite is also closely related to the compatibility of the fiber materials. The higher the compatibility, the higher the composite strength of the composite. Therefore, improving the compatibility of the fiber materials can significantly improve the composite strength of the hot-pressed composite. Thus, it is possible to significantly reduce the composite area while ensuring the composite strength of the 3D material, thereby significantly increasing the dust holding capacity of the material. This allows the 3D material to have both high composite strength and high dust holding capacity.

[0041] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Any simple modifications, alterations, and equivalent transformations made to the above embodiments based on the technical essence of the present invention shall still fall within the protection scope of the present invention.

Claims

1. A method for preparing a 3D filter material, characterized in that, The 3D filter material includes a composite end and a filter end adjacent to the composite end. The filter end includes several stacked fiber layers. The composite end is made by hot-pressing the fiber layers together. The preparation method includes the following steps: (1) 270 g of 1,4-butanediol, 300 g of terephthalic acid, 130 g of adipic acid, 80 g of isophthalic acid, 59 g of hexanediol, 36.03 g of acrylic acid and 0.34 g of tetrabutyl titanate were added to a reaction vessel to carry out a polymerization reaction to prepare copolymer PBT, wherein the melting point of the copolymer PBT is 150~160 °C; (2) The above-mentioned copolymer PBT is made into PBT meltblown cloth by meltblowing method, and PP is made into PP meltblown cloth by meltblowing method. PBT meltblown cloth, PP meltblown cloth and PBT meltblown cloth are stacked in sequence to form a preform. Then, the preform is hot-pressed and laminated with a patterned roller to form a 3D filter material. The hot-pressing temperature is 170 ℃ and the hot-pressing area accounts for 0.5%.

2. A method for preparing a 3D filter material, characterized in that, The 3D filter material includes a composite end and a filter end adjacent to the composite end. The filter end includes several stacked fiber layers. The composite end is made by hot-pressing the fiber layers together. The preparation method includes the following steps: (1) 270 g of 1,4-butanediol, 300 g of terephthalic acid, 130 g of adipic acid, 80 g of isophthalic acid, 47.2 g of hexanediol, 72.06 g of acrylic acid and 0.34 g of tetrabutyl titanate were added to a reactor to carry out a polymerization reaction to prepare copolymer PBT, wherein the melting point of the copolymer PBT is 150~160 °C; (2) The above-mentioned copolymer PBT is made into PBT meltblown cloth by meltblowing method, and PP is made into PP meltblown cloth by meltblowing method. PBT meltblown cloth, PP meltblown cloth and PBT meltblown cloth are stacked in sequence to form a preform. Then, the preform is hot-pressed and laminated with a patterned roller to form a 3D filter material. The hot-pressing temperature is 170 ℃ and the hot-pressing area accounts for 0.3%.

3. A method for preparing a 3D filter material, characterized in that, The 3D filter material includes a composite end and a filter end adjacent to the composite end. The filter end includes several stacked fiber layers. The composite end is made by hot-pressing the fiber layers together. The preparation method includes the following steps: (1) 270 g of 1,4-butanediol, 300 g of terephthalic acid, 130 g of adipic acid, 80 g of isophthalic acid, 52.44 g of hexanediol, 48.04 g of acrylic acid and 0.34 g of tetrabutyl titanate were added to a reaction vessel to carry out a polymerization reaction to prepare copolymer PBT, wherein the melting point of the copolymer PBT is 150~160 °C; (2) The above-mentioned copolymer PBT is made into PBT meltblown cloth by meltblowing method, and PP is made into PP meltblown cloth by meltblowing method. PBT meltblown cloth, PP meltblown cloth and PBT meltblown cloth are stacked in sequence to form a preform. Then, the preform is hot-pressed and laminated with a patterned roller to form a 3D filter material. The hot-pressing temperature is 170 ℃ and the hot-pressing area ratio is 0.1%.

4. The preparation method according to any one of claims 1 to 3, characterized in that, The polymerization reaction includes, in sequence, esterification, prepolymerization, and polycondensation.

5. The preparation method according to claim 4, characterized in that, The conditions for the esterification reaction include: a first-stage esterification reaction temperature of 160~190 ℃ and a first-stage esterification reaction time of 1~3 h; a second-stage esterification reaction temperature of 190~220 ℃ and a second-stage esterification reaction time of 1~2 h.

6. The preparation method according to claim 4, characterized in that, The conditions for the prepolymerization reaction include: a first-stage prepolymerization reaction temperature of 220~240 ℃, a first-stage prepolymerization reaction time of 0.5~1 h, and a first-stage prepolymerization reaction pressure of 1~10 kPa; a second-stage prepolymerization reaction temperature of 240~250 ℃, a second-stage prepolymerization reaction time of 0.5~1 h, and a second-stage prepolymerization reaction pressure of 0.5~1 kPa.

7. The preparation method according to claim 4, characterized in that, The conditions for the polycondensation reaction include: a polycondensation reaction temperature of 250~270 ℃, a polycondensation reaction pressure of 0.01~0.1 KPa, and a polycondensation reaction time of 1.5~3 h.

8. The preparation method according to any one of claims 1 to 3, characterized in that, Nitrogen gas is introduced into the reactor to purge the air from the reactor.

9. The preparation method according to any one of claims 1 to 3, characterized in that, The pressure in the reactor was increased to 0.1 MPa.

Citation Information

Patent Citations

  • Wiping cloth used for industry

    CN102162173B

  • Wiping cloth manufacturing method and wiping cloth

    CN112726058A

  • Laminated nonwoven fabric and its production

    JP1993321115A